Black tide son eaudiobook - Long, H.M (Winter Sea, 2024)
Samuel and Mary are thriving as privateers on the Winter Seas. As they navigate the complexities of their growing bond, in a world that would see Mary as chattel to be traded, the pair are forging a better way to live, under the sails of Hart. But when their latest prize brings tales of Benedict's capture by Mereish forces, they must make an impossible choice: to serve their nation or save Samuel's brother. Thrust into a mission of intrigue and infiltration, they seek to break into the most secure prison on the Mereish Coast. But as they sail deep into enemy territory, they find themselves hunted by a cunning and mysterious new foe—an enemy who seems to know their every secret, and who will kill to keep their own. As the Black Tide rises, and fleets take to the water, Samuel, Mary, and Benedict are on a desperate race for survival—both their own, and the free nations of the Winter Seas. "Daring escapes and high stakes on the high seas—half piratical fantasy, half familial intrigue, and all impossible to put down."—Allison Epstein, author of Let the Dead Bury the Dead